2018
DOI: 10.1016/j.cortex.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive coding in the human brain: Distinct object features are encoded by overlapping voxels in frontoparietal cortex

Abstract: Our ability to flexibly switch between different tasks is a key component of cognitive control. Non-human primate (NHP) studies (e.g., Freedman, Riesenhuber, Poggio, & Miller, 2001) have shown that prefrontal neurons are re-used across tasks, re-configuring their responses to code currently relevant information. In a similar vein, in the human brain, the "multiple demand" (MD) system is suggested to exert control by adjusting its responses, selectively processing information in line with our current goals (Dun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…Thus, our results suggest, first, that prefrontal representations carry action-oriented information during instruction following. This is line with previous studies that propose a crucial role of the frontolateral cortex in the integration of stimulus and response information into a task set based on verbal instructions 12,32,33 , as well as in representing task rules 17,24 and goals 34 . In contrast, parietal cortices contained both declarative and procedural information of relevant S-Rs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, our results suggest, first, that prefrontal representations carry action-oriented information during instruction following. This is line with previous studies that propose a crucial role of the frontolateral cortex in the integration of stimulus and response information into a task set based on verbal instructions 12,32,33 , as well as in representing task rules 17,24 and goals 34 . In contrast, parietal cortices contained both declarative and procedural information of relevant S-Rs.…”
Section: Discussionsupporting
confidence: 92%
“…As a first step, we investigated which brain regions were predominantly involved in instruction prioritization. Our intuition was that prioritization would boost implementation signals and, as such, we expected a frontoparietal network to be particularly crucial, as it is usually involved in the implementation of novel task sets 11,1417,24 . We thus established a set of a priori candidate regions that encompassed frontal (inferior and middle frontal gyri) and (inferior and superior) parietal cortices (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Duncan & Owen, 2000;Fedorenko et al, 2013) and have been posited to play a fundamental role in executive function and cognitive control (Corbetta & Shulman, 2002;Cole & Schneider, 2007). Non-human primate research has shown that these regions preferentially code task-relevant information (Rao, Rainer, & Miller, 1997;Freedman et al, 2001;Cromer et al, 2010;Roy et al, 2010;Kadohisa et al, 2013), a result mirrored in human neuroimaging data (Woolgar et al, 2015;Jackson et al, 2017;Jackson & Woolgar, 2018). This selective representation may support preferential coding in other brain regions (Desimone & Duncan, 1995;Miller & Cohen, 2001), as indicated by previous work (Baldauf & Desimone, 2014;Goddard, Carlson, & Woolgar, 2019), yielding a plausible mechanism for a brain-wide focus on relevant information and a key component of cognitive control.…”
Section: Discussionmentioning
confidence: 66%
“…MD ROIs were defined using co-ordinates from a previous review of activity associated with a diverse set of cognitive demands (Duncan & Owen, 2000) using the kernel method described in Cusack, Mitchell, and Duncan (2010) as in our previous work (Woolgar, Hampshire, Thompson, & Duncan, 2011;Woolgar, Thompson, Bor, & Duncan, 2011;Woolgar et al, 2015;Jackson et al, 2017;Jackson & Woolgar, 2018). We opted to use a template definition of the MD network because recent work has indicated that there is no particular benefit to using individual subject functional localisers to define these regions for multivariate analysis (Shashidhara, Spronkers, & Erez, 2019), whereas the template approach made it easy to compile the data across the group.…”
Section: Network Definitionmentioning
confidence: 99%
See 1 more Smart Citation